Comparative Assessment of Rapid Identification and Antimicrobial Susceptibility Testing Methods for Bloodstream Infections in a Non-24/7 Clinical Microbiology Laboratory - Sunggyun Park; Dohoon Kim; Namhee Ryoo (Microorganisms)
Rapid identification and antimicrobial susceptibility testing are essential for timely bloodstream infection (BSI) management. This study aimed to investigate the performance and turnaround time of multiple rapid diagnostic methods in a microbiology laboratory without 24/7 operation. This study included 236 positive blood culture bottles. Rapid identification methods were assessed with the SepsiTyper kit and the FilmArray blood culture identification 2 (BCID2) panel. Rapid antimicrobial susceptibility testing (AST) methods involved direct AST using the BD Phoenix M50 system and QuantaMatrix direct and rapid antimicrobial susceptibility testing (dRAST) and resistance gene detection with the FilmArray BCID2 panel. Conventional methods were used to compare results. The turnaround time was analyzed from blood culture positivity to preparation initiation and from preparation initiation to result reporting. Both rapid identification methods significantly reduced the turnaround time (~1 day and 19 h) compared to conventional identification. SepsiTyper demonstrated higher species-level accuracy in monomicrobial samples, whereas BCID2 outperformed in polymicrobial cases. Among the rapid AST methods, BCID2 and dRAST enabled result reporting within 24 h of positivity. Preparation delays were >45% of the overall turnaround time. Rapid diagnostics substantially shortened the BSI diagnostic time, even in limited-operation settings. Their clinical utility may be improved through 24/7 laboratory workflows.